Octavio Paz entre la literatura mundial y las literaturas del mundo - Müller, Gesine (iMex. México Interdisciplinario / Interdisciplinary Mexico, 2021)
pp. 51-63
The debate around the concept of world literature, held with new intensity in the last twenty years, is part, within the framework of cultural studies, of the controversies that are closely associated with issues related to global networks in a polycentric world. In view of this, this article would first of all like to open the field of tension between the concepts of world literature and literature of the world, with the purpose of developing differentiation criteria that will serve to illustrate the reception and canonization of the work of Octavio Paz, located in the middle of that field of tension.
Keywords: FOS: Languages and literature